From the Monster to the Kid Next Door: Transgender Children, Cisgender Parents, and the Management of Difference on TV - Prochuk, Alana (Atlantis, 2014)
This article explores the recent surge in television representations of transgender children. In particular, it analyzes episodes of The Tyra Show, Anderson, 20/20, Dr. Phil, and The Passionate Eye, arguing that these shows exploit the cultural symbolism of childhood to defuse the political challenge posed by trans subjectivity.